Uniform convergence of the Fourier-Laplace series - Rasedee A.F.N.B.; Rakhimov A.; Ahmedov A.A. (American Institute of Physics Inc., 2024)
This study examines the problem of uniform convergence for the functions from the Nikolskii class. The uniform convergences for the Riesz means of the Fourier-Laplace series in the Nikolskii class Hpa(SN) proved under certain conditions. 2017 Author(s).